The role of health literacy within the social determinants of health framework: a cross-sectional study on smoking behavior in Fujian, China - Chen, Zulin; Zheng, Yikun; Lin, Lihan; Chen, Yongjun; Zheng, Yunting; Chen, Hongmiao (Frontiers in Public Health, 2025)
BackgroundSmoking is a leading preventable cause of death, and its prevalence varies with social determinants of health (SDoH) such as education, age, and urban/rural residence. Health literacy (HL) may influence tobacco use, but its interplay with SDoH in China is unclear. This study examined associations between HL, key SDoH, and current smoking among residents aged 15–69 in Quanzhou, Fujian, China.MethodsA cross-sectional survey was conducted in 2024 among 3,200 residents of Quanzhou, Fujian Province, selected via multistage random sampling. Data on smoking status, health literacy, and SDoH were collected using the nationally standardised questionnaire developed by the Chinese Center for Health Education. Associations between smoking status, HL, and SDoH were analyzed using chi-square tests and multivariable logistic regression.ResultsOf 3,200 participants, the overall prevalence of current smoking was 25.680%, with significant gender differences (p < 0.001). Given the extremely low prevalence of current smoking among females (0.66%), the following results are based exclusively on male participants. Among males (n = 1,533), smoking prevalence was higher in rural areas (51.37%) than in urban areas (41.83%, p = 0.002), and increased with age, peaking at 58.74% among those aged 55–64 (p < 0.001). Smoking prevalence declined with higher educational attainment, from 54.27% in those with junior high school education to 18.380% in those with a bachelor’s degree or higher (p < 0.001). Multivariable logistic regression showed that age was associated with increased odds of smoking (e.g., OR = 5.699, 95% CI: 3.091–10.508 for ages 55–64 vs. 15–24; p < 0.001), and higher education was associated with reduced odds (e.g., bachelor’s degree vs. no formal education: OR = 0.180, 95% CI: 0.087–0.374; p < 0.001). Among HL dimensions, only inadequate practical health skills remained significantly associated with current smoking (OR = 1.358, 95% CI: 1.015–1.817; p = 0.039).ConclusionHL and SDoH jointly influenced smoking in Chinese men; low practical health skills and being older, less educated, or from a rural area were linked to higher risk. Strategies that enhance practical health skills and address social disparities may help reduce smoking, supporting Healthy China 2030 and WHO tobacco-control goals.